HIPERAKTIF, HUBUNGAN SOSIAL dan POLA ASUH ANAK TKW (STUDI DESKRIPTIF POLA ASUH dan PERKEMBANGAN SOSIO-EMOSIONAL ANAK TKW DI KABUPATEN LOMBOK TENGAH) - Arif Widodo; Setiani Novitasari; Dyah Indraswati; Nursaptini Nursaptini; Deni Sutisna (Universitas Kristen Satya Wacana, 2020)
ADHD is a psychological disorder in which a person has difficulty focusing andhyperactive behavior. Most of the ADHD students come from TKW families, with asignificant number in Central Lombok district. This study aims to examine the factorscausing the hyperactive behavior of TKW children. This research took place in a publicelementary school in the Batuk Liang area of Central Lombok district. This location waschosen because there were many students with special needs from TKW families, one ofwhom was experiencing hyperactivity. Through this research, the phenomenon of sensorydisturbance and hyperactivity among TKW children can be revealed. The subjects of thisstudy were children TKW who experienced hyperactivity, including: HN class V 12 yearsold, SP class VI 13 years old, SJM class V 11 years old, AN class VI 12 years old and KS classVI class 12 years old. The informants in this study were the caregivers of the TKWchildren and the teachers where the TKW children went to school. The method used inthis research is qualitative with a case study approach. Data collection was carried out byobservation and in-depth interviews. The research stages include preliminary studies,making instruments, data, analyzing data, and making research reports. The mainproblem in this study is how the socio-emotional development of TKW children so thatthey become hyperactive, how the family care patterns are applied and how the behaviorof TKW children in their daily lives. Based on the findings in the field and theoreticalstudies, it can be denied that hyperactive behavior is less due to the accumulation of innerconflicts caused by TKW children due to the love of their parents. The socio-emotionaldevelopment of TKW children began to be problematic since the mother left to becomeTKW. Grandma's inability to provide proper parenting and tend to give freedom to TKWchildren to behave inappropriately so that they have problems with their socialenvironment. As a result, these hyperactive TKW children have few friends because theyare ostracized. The behaviors shown by hyperactive TKW children include makingtrouble, engaging in acts of violence and other illegal acts